Role of discoidin domain receptor 2 (DDR2) and microRNA-182 in survival of women with high-grade serous ovarian cancer - Susana Ramalho; Liliana AL De Angelo Andrade; Cássio Cardoso Filho; Rodrigo de Andrade Natal; Marina Pavanello; Amanda Canato Ferracini; Luis Felipe Sallum; Luis Otávio Sarian; Sophie Derchain (Tumor Biology)
The objective of this study is to evaluate the relationship between discoidin domain receptor 2 (DDR2) and miR-182 expression with response to platinum-based chemotherapy and survival in women with high-grade serous ovarian cancer (HGSOC). We evaluated 78 women with HGSOC stages I-IV, diagnosed between 1996 and 2013, and followed up until 2016. DDR2 expression was assessed using immunohistochemistry on tissue microarray slides. The microRNAs were evaluated by qRT-PCR. DDR2 expression was high in 11 (14.1%) women. PFS was significantly lower in women with FIGO stage I/II – versus III/IV, post-surgery residual disease and high expression of DDR2. Women with postsurgery residual disease, FIGO stage I/II – versus III/IV and DDR2 expression had worse OS, but only post-surgery residual disease remained an independent prognostic factor for worse OS in multivariable analysis. miR-182 expression levels were significantly lower in patients harboring tumors with higher expression of DDR2 (p < 0.001). In this relatively large cohort of women with HSGOC, higher DDR2 expression was associated with lower miR-182 levels and worse PFS, suggesting that these molecules may be associated with mechanisms of HGSOC progression.